Chitosan-derived carbon supported ruthenium catalyst for efficient hydrogenation of levulinic acid to γ-valerolactone - Korampattu, Lavanya; Dhepe, Paresh L. (Sustainable Energy & Fuels, 2025)
The transition from fossil fuels to sustainable energy and chemical production relies heavily on efficient biomass valorization. Levulinic acid (LA), a key platform chemical from lignocellulosic biomass, serves as a versatile precursor for valuable chemicals like gamma-valerolactone (GVL), a promising green solvent, fuel additive, and polymer precursor. While ruthenium-based catalysts are effective for LA hydrogenation, conventional systems like Ru/C often suffer from metal leaching and deactivation due to weak metal-support interactions. Current approaches to improve stability, such as using nitrogen-doped carbon supports, involve complex synthesis and synthetic nitrogen precursors. Addressing these limitations, we present a facile and sustainable strategy for synthesizing a robust ruthenium catalyst by directly pyrolyzing marine biomass-derived chitosan to form a self-nitrogen-doped carbon support. This catalyst exhibited superior stability and excellent recyclability in the aqueous-phase hydrogenation of LA to GVL, surpassing conventional Ru/C while maintaining activity comparable to that of leading Ru catalysts supported on N-doped carbon. Unlike other N-doped carbon supports, our method avoids synthetic N-dopants and tedious procedures, making it inherently more sustainable. Detailed characterization via XPS and H2-TPR revealed strong metal-support interactions, facilitated by intrinsic nitrogen functionalities, effectively stabilizing the ruthenium species. This study also identifies the critical role of graphitic and pyridinic nitrogen species in controlling catalytic activity and elucidates the importance of optimizing nitrogen species and content in tailoring chitosan-derived supports. The proposed mechanism describes how Ru-N centers activate hydrogen and LA, with basic nitrogen sites aiding the dehydration step to GVL. Overall, this work features the potential of chitosan derived carbon as a sustainable and tunable support for efficient biomass hydrogenation catalysts and offers fundamental insights into the role of nitrogen doping in tailoring catalytic performance.